2017
DOI: 10.15640/jthm.v5n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Cruising Market in Oman: Current Trends and Future Perspectives

Abstract: The worldwide cruise industry has expanded over the past decades.For many countries, it has become a significant source of income. Cruising is considered as a holiday that gives a "flavour" of each country, albeit a brief one, so if interested, the country or region could be visited another time for longer period.Cruising companies have succeed in attracting more customer segments by offering a wide range of durations, itineraries, and prices. Prices vary according to the time of year, itinerary and level of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, researches differ on the duration of the vacation (Neuts et al, 2016;Atef & Balushi, 2017;Alén et al 2012). Our results show that 73.3% of seniors prefer a length of stay of 4 to 7 days.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…However, researches differ on the duration of the vacation (Neuts et al, 2016;Atef & Balushi, 2017;Alén et al 2012). Our results show that 73.3% of seniors prefer a length of stay of 4 to 7 days.…”
Section: Discussionmentioning
confidence: 47%
“…Regarding the length of stay of seniors in a destination, the general perception is that they have enough free time compared to other age groups and stay on holiday longer (de Oliveira Santos et al, 2014). Neuts et al (2016) revealed that seniors prefer longer trips (between 10 and 14 days), as opposed to non-seniors who require a duration of between 3 and 7 days (Atef & Balushi, 2017). However, some authors note that the length of stay for an older adult can range from 1 to 3 nights, 4 to 5 nights, or up to 9 nights.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…The reason behind this is that graduates of tourism guidance specialization cannot wok as tour guides unless they obtain a "Tour Guide Licence" from the Omani Ministry of Tourism. Tour guides working in Oman must pass an oral exam by the Tour Guide Committee of the Omani Ministry of Tourism, then be granted one of the following license categories (Omani Ministry of Tourism, 2016;Atef and Al-Balushi, 2017b):…”
mentioning
confidence: 99%